2013
DOI: 10.1038/bjc.2013.431
|View full text |Cite
|
Sign up to set email alerts
|

Notch-induced transcription factors are predictive of survival and 5-fluorouracil response in colorectal cancer patients

Abstract: Background:The purpose of this study was to evaluate the expression of Notch-induced transcription factors (NTFs) HEY1, HES1 and SOX9 in colorectal cancer (CRC) patients to determine their clinicopathologic and prognostic significance.Methods:Levels of HEY1, HES1 and SOX9 protein were measured by immunohistochemistry in a nonmalignant and malignant tissue microarray of 441 CRC patients, and the findings correlated with pathologic, molecular and clinical variables.Results:The NTFs HEY1, HES1 and SOX9 were overe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
51
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 50 publications
7
51
0
Order By: Relevance
“…The most investigated intestinal stem cell markers in a clinical setting are LGR5, 17,29-41 BMI1, 42-49 MSI1, 50-52 and SOX9. 5,28,[53][54][55][56][57][58][59][60][61] This review evaluates the potential clinical implications of these 4 putative intestinal stem cell markers and their potential role in human CRC.…”
Section: Introductionmentioning
confidence: 99%
“…The most investigated intestinal stem cell markers in a clinical setting are LGR5, 17,29-41 BMI1, 42-49 MSI1, 50-52 and SOX9. 5,28,[53][54][55][56][57][58][59][60][61] This review evaluates the potential clinical implications of these 4 putative intestinal stem cell markers and their potential role in human CRC.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, detecting cells positive for CD133, OCT4, and SOX2 after chemoradiotherapy confirmed the role of undifferentiated cancer cells in tumor recurrence [232]. Additionally, it has been proposed that SOX9 is involved in colon carcinogenesis and cancer progression, due to its overexpression in CRC tissues and cell lines [233][234][235][236].…”
Section: Colon and Rectummentioning
confidence: 83%
“…Among them, FOXA1, STAT3 and HEY1 were more important in the regulatory network. Candy et al (37) indicated that overexpressed HEY1 was a negative prognostic factor for colorectal cancer, and it is closely associated with vascular and perineural invasion and lymph node metastasis. Therefore, the upregulated HEY1 may be associated with OS metastasis.…”
Section: Discussionmentioning
confidence: 99%